The Effect Of Using Inference On Student’s Reading Comprehension Skill - yanto yanto (English Literature Department, Adab and Humanities Faculty, 2020)
The purpose of this experimental research was to find out the effetcs of using inference strategy on student’s reading comprehension skills. One participant was taught how to use think aloud and inference strategy while she was reading a text. Then, she was interviwed on her understanding of the text after using the inference strategy. The result showed that her test score before and after treatment was not significanly change. However, from the interview, the participant admitted that the strategy was very helpful in understanding a text in many different ways.